Can Biomimetic Superhydrophobic Surfaces Resist Underwater Biofouling? - Aijuan Deng; Zhixiong Liu; Yang Tang; Heting Hong (Proceedings)
In exploring the biofouling resistance capabilities of biomimetic superhydrophobic surfaces, femtosecond laser technology was employed to create these surfaces, leading to comprehensive anti-fouling efficacy evaluations [...]